EXPERIMENTAL VERIFICATION OF THE NEW MODELS APPLIED TO GLASS FIBRE REINFORCED CONCRETE (GFRC) CONFINED WITH GLASS FIBRE REINFORCED POLYMER (GFRP) COMPOSITES - Yahiaoui, Djarir; Mamen, Belgacem; Saadi, Mohamed; Bouzid, Tayeb (Ceramics-Silikáty, 2022)
External confinement by the GFRP composites offers an actual process for retrofitting glass fibre reinforced concrete columns (GFRC) subject to static or seismic loads. This paper presents an experimental investigation and analytical modelling of the axial compression of confined circular concrete columns of different strengths (8.5, 16, and 25 MPa). Furthermore, the columns contain different percentages of glass fibres (0.3 to 1.2 %), and their confinement is given by GFRP composites of various thicknesses (0.8 to 2.4 mm). The uniaxial compression test on these specimens reveals that the glass fibre percentage and the thickness of the GFRP play a vital role in improving the load-deformation behaviour and crack propagation. Whatever the concrete strength, the ultimate axial strain and stress predicted using the suggested confinement model almost agrees with the available experimental results.